Probability Multi-Valued Neutrosophic Sets for Improving Instructional Practices in College Civil and Commercial Law Courses: A Quality-Based Evaluation Approach - Qiang Zhang; Hongwei Liu; Haopeng Zhang (Neutrosophic Sets and Systems)
The evolving nature of legal education necessitates continuous improvement in instructional practices, particularly within core areas like civil and commercial law. As legal systems grow in complexity and relevance, higher education institutions must ensure that law students are not only well-versed in theory but also equipped with practical and analytical skills. This study proposes a quality-based evaluation framework to systematically assess and improve teaching strategies in civil and commercial law courses. Four key criteria curriculum relevance, instructional effectiveness, student engagement, and assessment quality—are employed to evaluate seven instructional alternatives ranging from traditional lectures to simulation-based learning. Utilizing neutrosophic set approach, the study identifies high-impact teaching practices that enhance student comprehension, critical thinking, and real-world readiness. We use the neutrosophic set to solve uncertainty problems. Probability Multi-Valued Neutrosophic Sets is used in this study with a set of definitions and operations. Results show that experiential and blended models outperform traditional formats, highlighting the need for pedagogical transformation. This research provides valuable insight for educators, academic planners, and legal training institutions striving for excellence in law education.